Perbedaan Kualitas Hidup Pasien COVID-19 dengan Cormobid - Linda Widiastuti (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the difference in the quality of life of COVID-19 patients with Comorbid in the Tanjungpinang City area. The research method uses analytical research with a comparative design. The results of the study were the majority of COVID-19 respondents with comorbid DM: age range 56-65 years 26 (50%), female sex 38 (73.1%), high school education 26 (50%), signs of COVID-19 symptoms (fever, cough, sore throat and shortness of breath) 52 (100%). While the majority of COVID-19 respondents with comorbid HT: age range 56-65 years 21 (26.9%), female sex 27 (51.9%), high school education 23 (44.2%), signs of COVID-19 symptoms (fever, headache) 52 (100%), blood sugar examination when abnormal with 43 people (82.7%). Blood pressure examination of stage 2 hypertension (â‰¥ 140/>90 mmHg) with a total of 26 people (50%). The results of the bivariate analysis of the Mann Whitney test showed that the Value was 0.001 (<0.05). In conclusion, there was a difference in the quality of life. COVID-19 patients with comorbid diabetes mellitus and hypertension. Keywords: COVID-19, Diabetes Mellitus, Hypertension, Quality of Life